2020
DOI: 10.2147/idr.s232169
|View full text |Cite
|
Sign up to set email alerts
|

<p>Eradication Treatment of <em>Helicobacter pylori</em> Infection Based on Molecular Pathologic Antibiotic Resistance</p>

Abstract: Background: Unfortunately, the eradication rate of Helicobacter pylori (H. pylori) treatment is markedly decreasing in recent years and the major reason is antibiotic resistance. Our study was designed to determine the effect and safety of H. pylori eradication treatment based on the molecular pathologic antibiotic resistance. Methods: 261 patients were analyzed retrospectively, including 111 patients who were treated for the first time (one group as First-treated) and 150 patients who failed at least once in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…However, culture has a high specificity and a relatively low sensitivity, and certain technique is required. 1 , 14 With the rapid development of molecular biology technology, some molecular markers have been used to predict H. pylori resistance, for example mutations of 23S rRNA, PBP1, gyrA and 16S rRNA for clarithromycin, amoxicillin, fluoroquinolone and tetracycline resistance, respectively. 14–17 Currently, molecular biology methods are practical for susceptibility testing.…”
Section: Introductionmentioning
confidence: 99%
“…However, culture has a high specificity and a relatively low sensitivity, and certain technique is required. 1 , 14 With the rapid development of molecular biology technology, some molecular markers have been used to predict H. pylori resistance, for example mutations of 23S rRNA, PBP1, gyrA and 16S rRNA for clarithromycin, amoxicillin, fluoroquinolone and tetracycline resistance, respectively. 14–17 Currently, molecular biology methods are practical for susceptibility testing.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study in Chile, 16 clarithromycin resistance was negatively correlated with the eradication rate (OR=0.13; 95% CI 0.04–0.49), ie, the eradication rate of patients being infected by clarithromycin-resistant H. pylori strains decreased significantly. The study by Gao et al 23 showed that according to the results of H. pylori resistance gene detection (amoxicillin PBP1 , clarithromycin 23S rRNA, levofloxacin gyrA , tetracycline 16S rRNA), 111 cases underwent initial treatment and 150 cases were treated again. The eradication rate in two groups was >90%, and no serious adverse event occurred.…”
Section: Discussionmentioning
confidence: 99%
“…An unprecedented number of studies last year reported on the important topic of antimicrobial resistance of H pylori strains 24‐60 . These are outlined in Table 1.…”
Section: Antibiotic Resistancementioning
confidence: 99%